Cancer Mortality Trends in Spain (2000–2016): Differences between Immigrant and Native Populations - Oliva-Arocas, Adriana (Int J Environ Res Public Health, 2020)
Spain’s population has changed thanks to recent immigration. Therefore, a new epidemiological and demographic profile has been generated in the country. This study aims to analyze immigrant and native cancer mortality trends in Spain for the period 2000 to 2016. An ecological study of trends was carried out. Age-standardized rates of cancer mortality (ASR) and annual percentage change (APC) between groups and study sub-periods were calculated. Significant decreases in ASR were observed for cancer in both the native and the immigrant populations, in both men and women. However, in 2014–2016, there was an increase in ASR in the immigrant population compared to 2011–2013, due to the increase in ASR among immigrants from European regions. Differences in ASR by cancer between immigrant and native populations residing in Spain have been identified, both in the rate of decline and magnitude as well as by the birth region of the immigrant population. The increase observed in the cancer mortality trend at the end of the period in some immigrant groups indicates the need to monitor these indicators given the demographic, social, and economic changes.